GENERAL ISSUES OF STUDENTS’ COGNITIVE ACTIVITY USING PROVERBS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article attempts to explore the use of proverbs, general issues of students’ cognitive activity, their place and role in the development of their vocabulary and consciousness, in upbringing and education. The correct use of proverbs in the classroom allows students to actively participate in the learning process and makes a great contribution to the development of their thinking, comparison, analysis and decision-making skills. The importance of creative cognitive activity lies not only in its influence on the solid acquisition of knowledge and deep thinking, but also in the formation of a person’s worldview and the accumulation of social experience. Teachers, in addition to analyzing the cognitive nature of students, also take on the task of forming psychological foundations.
Keywords: wise words, cognitive activity, vocabulary of students, speech development, education, knowledge, scientific knowledge, aphorisms, quotes, folklore, folk oral creativity, didactics, ethnopedagogy, language, riddles, tongue twisters, etc.